The potentiality of bioethanol production from corn (Zea mays L.) as a renewable source - Yesmin, M. N.; Azad, M. A. K.; Kamuruzzaman, M.; Ali, S. (Journal of Ecobiotechnology, 2020)
Corn (Zea mays L.) is one of the versatile crop which is used as food, feed, fodder and in recent past as a source of bio-fuel. The sub-tropical climate is very favorable for corn cultivation. Traditionally, corn was grown in South and Southeast Asia primarily as a subsistence food crop. Worldwide it is being cultivated in over 170 countries representing an area of 185 million ha with a productivity of 5.62 t ha-1 (FAO, 2017). Out of world corn production of 1037 million MT, SAARC countries comprising of Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka represent 3.2 % with a productivity of 3.8 t ha-1. Among SAARC countries, the highest productivity of 6.9 t ha-1 is reported in Bangladesh. Corn can be an important renewable source for bioethanol production. This research was carried out to evaluate Bangladeshi Corn for optimum bioethanol production. A 100 g of corn flour was mixed with 300 ml distilled water was blended and sterilized. The experiment was conducted with a temperature of 30 oC, pH 6.0 and 20 % sugar concentration. For alcoholic fermentation, 200 ml yeast (Saccharomyces cerevisiae CCD) was added to make the total volume 500 ml. Addition of small amount of 1750 unit α-amylase enzyme to the substrate solution was found to enhance the fermentation process quicker. After 6-days of incubation time corn produces 63.57 ml of ethanol with 13.33 % (v/v) purity. The non-filtered solution produces comparatively more ethanol (63.57 ml with 13.33 % purity) than the filtered solution (53.66 ml with 10 % purity). The purity can be increased by re-distillation process.